ANALISIS KESULITAN MENULIS SISWA KELAS RENDAH PADA PEMBELAJARAN BAHASA INDONESIA KELAS I DI SD 005 LANGGINI - Nurhaswinda; Hayatun Nupus; Ledy Mardhotillah Nasmai; Mifta Hurrahma; Sinta Rahmadani; Tia Rama Danti; Vina Aidil Fitri (STKIP Subang, 2025)
Writing is a language skill used for indirect communication through the use of language patterns such as graphology, language structure, and vocabulary. This study examines the writing difficulties experienced by lower-grade students in Indonesian language learning at SDN 005 Langgini, specifically in Grade I. The purpose of this research is to describe the writing difficulties faced by lower-grade students in learning the Indonesian language. This research employs a qualitative approach with a descriptive analysis method. Data were collected through tests, observations, interviews, and documentation. The results of the study show that out of 27 first-grade students at SDN 005 Langgini, 3 students experienced writing difficulties in their Indonesian language learning. Based on the research data, it can be concluded that the writing difficulties in lower-grade students at SDN 005 Langgini include: illegible handwriting, taking a long time to write which causes them to fall behind, writing letters or numbers that are slanted or unclear, and incorrect pencil grip.